Flexible electronic device with single-walled carbon nanomaterial modified metal copper attached polymer substrate and preparation method of flexible electronic device

By attaching metal copper to the polymer base film and using single-wall carbon nanotube modified materials, copper/carbon nanotube composite materials are prepared, which solves the problem that the material conductivity, flexibility and stability in the prior art is difficult to meet simultaneously. , realizes efficient preparation of flexible electronic devices.

CN119418987APending Publication Date: 2025-02-11厦门华碳科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411538221.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art When preparing flexible electronic devices, the conductivity, flexibility and stability of the materials are difficult to meet at the same time, especially when applying the requirements and design requirements of devices in different fields.

Method used

Copper/carbon nanotube composite material was prepared by attaching metal copper to the polymer base film and modifying the material using single-wall carbon nanotubes. This material achieves good conductivity, flexibility and stability through a combination of a stacked polymer base film, a photocuring resin layer, a copper layer and a copper/carbon nanotube composite layer.

Benefits of technology

The composite material significantly improves electrical, thermal and mechanical properties, and is suitable for the preparation of flexible electronic devices, meeting the multiple performance needs of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119418987A_ABST
    Figure CN119418987A_ABST
Patent Text Reader

Abstract

According to the flexible electronic device with the single-walled carbon nanomaterial modified metal copper attached to the polymer substrate and the preparation method of the flexible electronic device, a single-walled carbon nanotube is treated with a strong oxidant, the single-walled carbon nanotube is oxidized and stripped, a high-dispersity single-walled carbon nanotube aqueous solution is obtained, the surface of the polymer-based film substrate is coated with light-cured resin, and the flexible electronic device is obtained. Performing exposure curing to form a light-cured resin layer; immersing the polymer base membrane into the alkaline copper sulfate electroplating solution, and plating copper for a period of time by adopting a pulse electrodeposition method to obtain a composite copper material; adding the stripped single-walled carbon nanotube dispersion liquid into an electroplating solution to prepare a copper sulfate electroplating solution; codepositing copper and oxidized and stripped carbon nanotubes by adopting a pulse electrodeposition method to prepare a precursor of the composite material; and finally, carrying out annealing treatment to obtain the copper / carbon nanotube composite material. The carbon nanotubes in the composite material are uniformly distributed in a copper matrix, so that the electrical, thermal and mechanical properties of the composite material are remarkably improved, and the composite material is suitable for preparing flexible electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of composite metal conductive materials, and in particular relates to a flexible electronic device with single-walled carbon nanomaterial-modified metal copper attached to a polymer substrate and a preparation method thereof. Background Art

[0002] Copper metal materials are widely used in electrical conduction and the preparation of flexible electronic devices. In terms of conduction, copper, as an excellent electrical conductor, can be used to manufacture conductive components in various electronic devices such as wires, cables, and circuit boards. It has excellent electrical and thermal conductivity. In the preparation of flexible electronic devices, copper has good plasticity and elasticity and can be used to make flexible circuits, such as flexible displays, flexible sensors, and wearable devices. It plays an important role in realizing bendable and rollable electronic devices. With its superior conductivity and flexibility, copper metal provides many innovative application possibilities in the field of flexible electronics.

[0003] Carbon nanotubes have excellent conductivity and toughness and are widely used in the field of conductivity. As a nanoscale material, carbon nanotubes can be used as conductive wires or conductive paths in electronic devices, and can achieve efficient electron transmission through their high conductivity and small size. Carbon nanotubes can also be used to prepare flexible electronic devices, such as flexible displays, smart sensors, etc., and use their toughness and bendability to realize bendable and stretchable electronic devices. In addition, carbon nanotubes also have unique optoelectronic properties and can be used in optoelectronic devices and photocatalysis. Overall, the diverse applications of carbon nanotubes in the field of conductivity make them a very promising material. Single-walled carbon nanotubes have some significant advantages over multi-walled carbon nanotubes. First, single-walled carbon nanotubes are generally more conductive. Because their structure consists of only one layer of carbon atoms, the transmission path of electrons in single-walled carbon nanotubes is shorter, and electrons can pass through the tube more quickly, so the conductivity is higher. Secondly, single-walled carbon nanotubes are small in size. Because their diameter is only a few nanometers, single-walled carbon nanotubes can be used as very small conductive paths, which is very beneficial for the manufacture and integration of microelectronic devices. In addition, single-walled carbon nanotubes also have good mechanical properties, high toughness and strength, and can play an excellent conductive role in flexible electronic devices. In summary, single-walled carbon nanotubes have broad application prospects in the field of conductivity due to their good conductivity, small size and good toughness.

[0004] Chinese invention patent CN112865239A discloses a preparation method and device of a wireless charging device that can be sewn on fabrics, which includes: immersing copper-carbon nanotube fibers in a polyamic acid solution and taking them out; performing imidization treatment on the copper-carbon nanotube fibers to obtain polyimide-copper-carbon nanotube fibers; forming coil-shaped patterns on the fabric by embroidery or sewing the obtained polyimide-copper-carbon nanotube fibers. The present invention solves the problem of material limitations, and utilizes the flexibility, lightness, and spinnability of carbon nanotube fibers to integrate them into fabrics; solves the disadvantage of poor conductivity of carbon nanotube fibers, and makes their conductivity close to that of copper by copper plating, greatly improving the charging efficiency; solves the disadvantages of insulation and washability of silk-wrapped carbon nanotube wires, and applies a polyimide paint coating to form a uniform, well-insulated, and washable carbon nanotube enameled wire. Since the copper-carbon nanotube fibers are wrapped with a polyimide paint coating, their applications are limited, especially the inability to meet the requirements of specific patterns or structures to meet the needs and design requirements of devices in different fields. Summary of the invention

[0005] In order to achieve the above-mentioned purpose, the present application provides a flexible electronic device with metal copper attached to a polymer base film, and uses single-walled carbon nanotubes for material modification to achieve the preparation of a copper / carbon nanotube composite material suitable for flexible electronic devices on the polymer base film. This material not only has good electrical conductivity, but also provides flexibility and stability, thereby meeting the material requirements of flexible electronic devices.

[0006] The first aspect of the present application provides a flexible electronic device with a single-walled carbon nanomaterial modified metallic copper attached to a polymer substrate, comprising a stacked polymer base film, a photocurable resin layer, a copper layer and a copper / carbon nanotube composite layer.

[0007] In any embodiment, the polymer base film is a polyimide film.

[0008] In any embodiment, the coating dry weight of the photocurable resin layer is 0.2-1 g / cm 2 The best is 0.2-0.5g / cm 2 .

[0009] The second aspect of the present application also provides a method for preparing a flexible electronic device with a single-walled carbon nanomaterial modified metal copper attached to a polymer substrate, comprising the following steps:

[0010] 1) treating the single-walled carbon nanotubes with a strong oxidant to obtain a highly dispersed single-walled carbon nanotube aqueous solution;

[0011] 2) coating the surface of the pre-treated polymer base film with a photocurable resin and curing it to form a stable base film;

[0012] 3) using pulse electrodeposition technology to plate copper on the base film for a period of time to form a composite copper material;

[0013] 4) adding the single-walled carbon nanotube aqueous solution into the electroplating solution, and using pulse electrodeposition technology to co-deposit the single-walled carbon nanotube aqueous solution with copper ions to form a precursor;

[0014] 5) The precursor is annealed to obtain a copper / carbon nanotube composite material.

[0015] In any embodiment, in step 1), after adding single-walled carbon nanotubes to the mixed acid and stirring evenly, perchloric acid or nitric acid is added batch by batch and stirring is continued until a suspension is obtained; the suspension is heated and kept at 50-100° C. for 0.5-12 hours, then cooled to room temperature, and poured into distilled water containing chromic acid; thereafter, the acid is removed by centrifugation, and then washed with sulfuric acid to remove impurities; finally, the composite is dispersed in deionized water and filtered until neutral to obtain an oxidatively exfoliated carbon nanotube dispersion.

[0016] In any embodiment, the mixed acid consists of hydrochloric acid and phosphoric acid, the strong oxidant is at least one of perchloric acid, nitric acid and chromic acid; the mass volume ratio of the single-walled carbon nanotubes to the mixed acid, perchloric acid, nitric acid and chromic acid is 1g:100-600mL:1-8mL:30-50mL:4-25mL.

[0017] In any embodiment, in step 2), the polymer base film is a polyimide (PI) film; the PI film is prepared by immersing it in an ethanol aqueous solution of 1-3M KOH and 0.5-2M NaHCO3, wherein the volume ratio of ethanol to water is 1-3:1, and pre-treating it for 30-60 minutes; then, a photocurable resin with a dry weight of 0.2-1g / cm2 is coated on the surface of the PI film, and the film is cured under ultraviolet light for 1-3 hours to form a stable base film.

[0018] In any embodiment, in step 2), the photocurable resin is shielded by a light-shielding mask or template to form a photocurable area with a certain pattern or structure.

[0019] In any embodiment, in step 2), a colloidal solution containing noble metal acetate and noble metal chloride is coated on the photocurable resin and dried again.

[0020] In any embodiment, the colloidal solution, take 1g of palladium acetate, first dissolve it in 3M hydrochloric acid, and then dilute it to 120mL with deionized water to prepare a precious metal precursor solution. 100mL of ethylene glycol solution is preheated to 110°C, stirred and heated for 3h, then 10mL of precious metal precursor solution is slowly injected, sodium dodecylbenzene sulfonate (SDBS) with a mass ratio of 2 to palladium is added, and heating is continued for 1h. Then 4mL of 80M sodium bisulfite is added and heated for another 30 minutes to obtain a solution containing palladium nanoparticles. The nanoparticles are separated by a high-speed centrifuge, washed with alcohol and water, and finally dispersed into 10mL of colloidal dispersion by ultrasound.

[0021] In any embodiment, in step 3), a titanium plate with surface polishing is selected as the working electrode, and a copper plate is selected as the counter electrode. Electroplating is performed using a copper sulfate electroplating solution with a pH value of 7-9, and copper is deposited on the PI film using a pulse electrodeposition method.

[0022] In any embodiment, in step 3), the oxidized exfoliated carbon nanotube dispersion is added to the electroplating solution, and is uniformly dispersed by ultrasonic and magnetic stirring for 30-60 minutes each. Finally, a copper / carbon nanotube composite precursor is prepared by pulse electrodeposition, and the electroplating solution is replaced regularly.

[0023] In any embodiment, EDTA, citric acid, cyclohexane polycarboxylic acid or agarose complexing agent is added to the copper sulfate electroplating solution.

[0024] In any embodiment, the pulse electrodeposition has a forward current density range of 20-600mA / cm6, a pulse width of 800-6000μs, a reverse current density of -0.2--22mA / cm6, a pulse width of 10-2000μs, a duty cycle of 3%-25%, and a deposition time of 0.1-20h.

[0025] In any embodiment, the deposition time of step 3) is 10 min, and the deposition time of step 4) is 10-60 min.

[0026] In any embodiment, the annealing temperature of the precursor is 500-900°C.

[0027] Beneficial effects of the present application: The application forms an activated photocurable resin layer by coating a photocurable resin coating on the surface of a polymer base film, and then performing exposure curing; then immersing the polymer base film in an alkaline copper sulfate electroplating solution, and copper plating is performed for a period of time by pulse electrodeposition to obtain a composite copper material, and then adding the peeled single-walled carbon nanotube dispersion to the electroplating solution, and co-depositing copper and oxidized peeled carbon nanotubes by pulse electrodeposition to prepare a precursor of the composite material; finally, after annealing, a copper / carbon nanotube composite material is obtained, and a composite flexible electronic device composed of a PI film-photocurable resin layer-copper-copper / carbon nanotube is obtained. In the composite material, carbon nanotubes are uniformly distributed in the copper matrix, which significantly improves its electrical, thermal and mechanical properties. The composite copper material with strong conductivity is particularly suitable for preparing flexible electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the structure of the flexible electronic device prepared by the present invention.

[0029] Explanation of the reference numerals: 1. PI film; 2. Photocurable resin layer; 3. Copper layer; 4. Copper-single-walled carbon nanotube layer. DETAILED DESCRIPTION

[0030] Hereinafter, the embodiments of the flexible electronic device of the single-walled carbon nanomaterial modified metal copper attached to the polymer substrate and the preparation method thereof of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0031] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0037] A flexible electronic device with single-walled carbon nanomaterial modified metal copper attached to a polymer substrate comprises a polymer base film, a photocurable resin layer, a copper layer and a copper / carbon nanotube composite layer arranged in layers.

[0038] Polyimide (PI) film plays a key role in the preparation of composite copper foil. Its high temperature resistance, chemical corrosion resistance, excellent electrical insulation, good adhesion performance and light and thin characteristics together ensure that the composite copper foil can work stably in various harsh environments, and is also conducive to the manufacture of lightweight electronic equipment.

[0039] The photocurable resin layer plays a key role in flexible electronic devices composited with copper foil, including providing good adhesion, being able to harden quickly under light, forming a protective layer that is corrosion-resistant and electrically insulating, and also has the potential to create innovative applications with specific patterns or structures.

[0040] In some embodiments, the coating dry weight of the photocurable resin layer is 0.2-1 g / cm 2 .

[0041] The coating dry weight of the photocurable resin layer needs to be evenly and fully coated on the surface of the copper foil during the preparation process of the composite copper foil to ensure that the requirements of coating uniformity and coverage are met; the coating dry weight of the photocurable resin layer is set within the above range to ensure that the physical properties of the composite copper foil are fully met. If the coating dry weight is too light, the resin layer may be too thin, resulting in insufficient strength and easy breakage or peeling. If the coating dry weight is too heavy, the resin layer may be too thick, affecting the electrical or thermal conductivity. In addition, too heavy a coating dry weight will increase the use of raw materials and production costs, and may reduce production efficiency, while too light a coating dry weight may require multiple coatings to meet the requirements, which will also increase production time and cost.

[0042] The second aspect of the present application also provides a method for preparing a flexible electronic device with a single-walled carbon nanomaterial modified metal copper attached to a polymer substrate, comprising the following steps:

[0043] 1) treating the single-walled carbon nanotubes with a strong oxidant to obtain a highly dispersed single-walled carbon nanotube aqueous solution;

[0044] 2) coating the surface of the pre-treated polymer base film with a photocurable resin and curing it to form a stable base film;

[0045] 3) using pulse electrodeposition technology to plate copper on the base film for a period of time to form a composite copper material;

[0046] 4) adding the single-walled carbon nanotube aqueous solution into the electroplating solution, and using pulse electrodeposition technology to co-deposit the single-walled carbon nanotube aqueous solution with copper ions to form a precursor;

[0047] 5) The precursor is annealed to obtain a copper / carbon nanotube composite material.

[0048] In some embodiments, in step 1), after adding single-walled carbon nanotubes to the mixed acid and stirring evenly, perchloric acid or nitric acid is added batch by batch and stirring is continued until a suspension is obtained; the suspension is heated and kept at 50-100° C. for 0.5-12 hours, then cooled to room temperature, and poured into distilled water containing chromic acid; thereafter, the acid is removed by centrifugation, and then washed with sulfuric acid to remove impurities; finally, the complex is dispersed in deionized water and filtered until neutral to obtain an oxidatively exfoliated carbon nanotube dispersion.

[0049] The reaction rate can be effectively controlled by gradually adding perchloric acid or nitric acid in batches, avoiding a violent reaction process and ensuring the safety and stability of the reaction. However, carbon nanotubes have a strong tendency to aggregate and accumulate. If all perchloric acid or nitric acid is added to the mixed acid at once, it may cause a large number of carbon nanotubes to aggregate together and be difficult to disperse evenly. Gradually adding perchloric acid or nitric acid in batches and continuing to stir can better achieve the dispersion of carbon nanotubes and make them evenly suspended in the solution.

[0050] In some embodiments, the mixed acid consists of hydrochloric acid and phosphoric acid, the strong oxidant is at least one of perchloric acid, nitric acid and chromic acid; the mass volume ratio of the single-walled carbon nanotubes to the mixed acid, perchloric acid, nitric acid and chromic acid is 1g:100-600mL:1-8mL:30-50mL:4-25mL.

[0051] Advantages of strong oxidants such as perchloric acid, chromic acid, and nitric acid: Higher oxidation efficiency. Due to their strong oxidizing ability, they can more effectively remove impurities in single-walled carbon nanotubes; Lower by-products. Compared with potassium permanganate and hydrogen peroxide, perchloric acid, nitric acid, and chromic acid tend to produce fewer by-products during the reaction, which means less waste and better environmental protection; Higher product purity. Due to their good removal effect on impurities, single-walled carbon nanotubes with higher purity can be obtained.

[0052] In some embodiments, in step 2), the polymer base film is a polyimide (PI) film; the PI film is prepared by immersing it in a solution of 1-3M KOH and 0.5-2M NaHCO3 in an ethanol aqueous solution with a volume ratio of ethanol to water of 1-3:1 for 30-60 minutes; then a coating with a dry weight of 0.2-1 g / cm 2 Light-curing resin, cures under ultraviolet light for 1-3 hours to form a stable base film.

[0053] The surface pretreatment of PI film (polyimide film) is an important step to improve its surface energy, increase surface roughness and change surface chemical properties to achieve better coating adhesion, printing effect or bonding with other composite materials. Using alkaline substances for the pretreatment of PI film can bring the following significance:

[0054] Increase surface roughness: Alkaline treatment can slightly corrode the surface of the PI film, making it rough. This surface roughening is conducive to better embedding and bonding of subsequent coatings or other materials with the PI film.

[0055] Improve surface energy: PI film itself has a low surface energy, which makes it difficult for many coatings and adhesives to form good adhesion with it. Through alkaline treatment, polar groups such as hydroxyl (-OH) can be introduced on the surface of PI film, thereby increasing its surface energy and improving the adhesion performance of coatings or adhesives.

[0056] Changing surface chemical functional groups: Alkaline treatment can introduce or expose new functional groups, which can react or form chemical bonds with materials in subsequent applications, improving the chemical bonding strength of the interface.

[0057] Clean surface: Alkaline solution can also remove oil, dust or other impurities on the surface of PI film, ensuring the surface is clean after treatment, which is beneficial to improve the overall quality of the product.

[0058] Therefore, the pretreatment of alkaline substances can not only improve the application performance of PI film through surface modification, but also help improve the reliability and durability of the product. However, when performing this treatment step, the control of parameters such as the concentration of alkaline substances, treatment time and temperature must also be considered to avoid excessive corrosion or damage to the basic properties of the PI film.

[0059] In some embodiments, in step 2), the photocurable resin is shielded by a light-shielding mask or template to form a photocurable area with a certain pattern or structure.

[0060] Photocurable resins can be formed into special patterns by using light-shielding masks or templates in specific areas. These light-shielding masks or templates can block ultraviolet light so that the resin can only be cured in areas that are not shielded from light. By using different light-shielding masks or templates, patterns of various shapes and structures can be achieved.

[0061] The photocurable resin layer provides good adhesion and can firmly bond the composite copper foil to the substrate, ensuring the stability and reliability of the composite material. Secondly, the photocurable resin can quickly harden under ultraviolet light to form a corrosion-resistant and electrically insulating protective layer to protect the composite copper foil from erosion and damage from the external environment. Finally, through the photocurable resin layer, innovative applications with specific patterns or structures can be created to meet the needs and design requirements of different fields.

[0062] In some embodiments, in step 2), a colloidal solution containing noble metal acetate and noble metal chloride is coated on the photocurable resin and dried again.

[0063] In some embodiments, the colloidal solution, take 1g of palladium acetate, first dissolve it in 3M hydrochloric acid, and then dilute it to 120mL with deionized water to prepare a precious metal precursor solution. 100mL of ethylene glycol solution is preheated to 110°C, stirred and heated for 3h, then 10mL of precious metal precursor solution is slowly injected, sodium dodecylbenzene sulfonate (SDBS) with a mass ratio of 2 to palladium is added, and heating is continued for 1h. Then 4mL of 80M sodium bisulfite is added and heated for another 30 minutes to obtain a solution containing palladium nanoparticles. The nanoparticles are separated by a high-speed centrifuge, washed with alcohol and water, and finally dispersed into 10mL of colloidal dispersion by ultrasonic wave.

[0064] On the one hand, the colloidal solution contains noble metal acetates and noble metal chlorides, which react with the surface of the photocurable resin to cause surface chemical modification; this modification can improve the adhesion and oxidation resistance of the photocurable resin, making it more suitable for subsequent coating and curing steps.

[0065] On the other hand, the presence of noble metal acetate and noble metal chloride can improve the conductivity of the photocurable resin; in the process of coating the colloidal solution, the noble metal particles in the colloid can be evenly dispersed in the resin to form a conductive network; this improvement in conductivity can improve the conductive properties of the copper foil.

[0066] On the other hand, when the colloidal solution solidifies, a conductive film is formed on the coating layer; this conductive film can realize the effective transfer of current on the surface of the copper foil, playing the role of connecting circuits and conducting electrical signals.

[0067] Therefore, coating the colloidal solution containing noble metal acetate and noble metal chloride plays an important role in surface modification, conductivity improvement and conductive layer formation in the process of preparing the copper foil.

[0068] In some embodiments, in step 3), a titanium plate with a surface polishing treatment is selected as the working electrode, and a copper plate is selected as the counter electrode; copper sulfate electroplating solution with a pH value of 7-9 is used for electroplating, and pulse electrodeposition is used to deposit copper on the PI film.

[0069] The alkaline environment can reduce the competition for hydrogen ions in the plating solution, thereby effectively controlling the internal stress and gloss of the coating.

[0070] It has good ductility and flexibility and is suitable for applications requiring a certain toughness and fatigue resistance. Alkaline systems can provide a more uniform coating distribution in some cases.

[0071] Therefore, copper plating under alkaline conditions of copper sulfate solution with pH = 7-9 is more suitable for the preparation of flexible electronic devices.

[0072] Furthermore, since the PI film has been treated with alkali, if it is in an acidic electroplating solution, it is easy to cause serious corrosion on the surface of the PI film, and even damage the performance of the material itself, which will reduce the mechanical properties and mechanical properties of the PI film.

[0073] In some embodiments, in step 3), the oxidized exfoliated carbon nanotube dispersion is added to the electroplating solution and uniformly dispersed by ultrasonic and magnetic stirring for 30-60 minutes each. Finally, a copper / carbon nanotube composite precursor is prepared by pulse electrodeposition, and the electroplating solution is replaced regularly.

[0074] In some embodiments, EDTA, citric acid, cyclohexane polycarboxylic acid or agarose complexing agent is added to the copper sulfate electroplating solution.

[0075] The complexing agent can form a stable complex with the copper ions, reducing the concentration of the free copper ions, thereby slowing down the formation of copper hydroxide; the stable complexing agent is used to maintain the copper ions from being precipitated under the pH conditions.

[0076] In some embodiments, the pulse electrodeposition has a forward current density range of 20-600 mA / cm6, a pulse width of 800-6000 μs, a reverse current density of -0.2--22 mA / cm6, a pulse width of 10-2000 μs, a duty cycle of 3%-25%, and a deposition time of 0.1-20 h.

[0077] In some embodiments, the deposition time of step 3) is 10 min, and the deposition time of step 4) is 10-60 min.

[0078] The amount of single-walled carbon nanotubes added to the composite copper foil does not need to be too much. The purpose of electroplating a layer of single-walled carbon nanotube-copper composite material on the copper surface is to enhance the conductivity of the surface of the flexible electronic device.

[0079] Single-walled carbon nanotubes have a better advantage in improving electrical conductivity. Compared with the composite copper foil prepared by multi-walled carbon nanotubes, its tensile strength is increased by 5.8% and its resistivity is increased by 14.5%. In the pulse electrodeposition copper plating, the experimental time of the copper-plated substrate is 10 minutes, and the secondary copper plating time during the second pulse electrodeposition process is 10-60 minutes. The shorter and thinner copper layer has better ductility and conductivity.

[0080] In some embodiments, the annealing temperature of the precursor is 500-900°C.

[0081] High-temperature calcination annealing treatment to promote dispersion: high-temperature calcination can help carbon nanotubes disperse more evenly in the copper matrix, thereby improving the performance of the composite material; enhance adhesion: this treatment process can increase the bonding force between copper and carbon nanotubes, enabling them to form a more stable composite material; improve performance: high-temperature calcination can improve the thermal conductivity, electrical conductivity and other properties of the composite material; form special structures: during the calcination process, the material may form some special microstructures (such as pores), which may be helpful for manipulating the performance of the composite material.

[0082] Example

[0083] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0084] Embodiment 1:

[0085] First, 0.1 g of single-walled carbon nanotubes was added to 30 mL of mixed acid and stirred evenly, and then 4 g of perchloric acid was added batch by batch and stirred continuously until a suspension was obtained. The suspension was heated and kept warm at 50-100 ° C for 0.5-12 h, then cooled to room temperature and poured into 100 mL of distilled water containing 1 mL of chromic acid. After that, the acid was removed by centrifugation and then washed with sulfuric acid to remove impurities. Finally, the complex was dispersed in deionized water and filtered to neutrality to obtain a 1 mg / mL distilled water dispersion of oxidized exfoliated carbon nanotubes.

[0086] Prepare an ethanol aqueous solution of 2M KOH and 0.5M NaHCO3, with a volume ratio of ethanol to water of 3:1. Immerse the polyimide PI film in the aforementioned solution for pretreatment for 30 minutes. Coat the PI surface with 0.4g / cm6 photocurable resin. Curing the photocurable resin under ultraviolet light for 2 hours to form a stable base film. Coat a colloidal solution containing noble metal acetate and noble metal chloride on the photocurable resin and dry it again.

[0087] Use pulsed electroplating technology to plate copper on the base film. Set the forward current density to 100mA / cm6, the pulse width to 3000μs, the reverse current density to -40mA / cm6, the pulse width to 3000μs, and the duty cycle to 20%. Carry out plating for 10 minutes to form a composite copper material. Mix 100mL of the single-walled carbon nanotube aqueous solution with the plating solution containing 60g / L copper ions, and control the pH value of the plating solution to 8.

[0088] Single-walled carbon nanotubes and copper ions were co-deposited on the base film using pulsed electrodeposition technology. The forward current density was set to 100mA / cm6, the pulse width was selected to 3000μs, the reverse current density was -40mA / cm6, the pulse width was 3000μs, the duty cycle was selected to 20%, and the deposition time was 10min. The precursor was annealed in a nitrogen atmosphere, the annealing temperature was set to 600℃, and the temperature was naturally cooled. After annealing, a copper / carbon nanotube composite material was formed with uniform distribution and excellent performance.

[0089] Embodiment 2:

[0090] First, 0.1 g of single-walled carbon nanotubes was added to 30 mL of mixed acid and stirred evenly, and then 4 g of perchloric acid was added batch by batch and stirred continuously until a suspension was obtained. The suspension was heated and kept warm at 50-100 ° C for 0.5-12 h, then cooled to room temperature and poured into 100 mL of distilled water containing 1 mL of chromic acid. After that, the acid was removed by centrifugation and then washed with sulfuric acid to remove impurities. Finally, the complex was dispersed in deionized water and filtered to neutrality to obtain a 2 mg / mL distilled water dispersion of oxidized exfoliated carbon nanotubes.

[0091] Prepare an ethanol aqueous solution of 2M KOH and 0.5M NaHCO3, with a volume ratio of ethanol to water of 3:1. Immerse the polyimide PI film in the aforementioned solution for pretreatment for 30 minutes. Coat the PI surface with 0.4g / cm6 photocurable resin. Curing the photocurable resin under ultraviolet light for 2 hours to form a stable base film. Coat a colloidal solution containing noble metal acetate and noble metal chloride on the photocurable resin and dry it again.

[0092] Use pulsed electroplating technology to plate copper on the base film. Set the forward current density to 100mA / cm6, the pulse width to 3000μs, the reverse current density to -40mA / cm6, the pulse width to 3000μs, and the duty cycle to 20%. Carry out plating for 10 minutes to form a composite copper material. Mix 100mL of the single-walled carbon nanotube aqueous solution with the plating solution containing 60g / L copper ions, and control the pH value of the plating solution to 8.

[0093] Single-walled carbon nanotubes and copper ions were co-deposited on the base film using pulsed electrodeposition technology. The forward current density was set to 100mA / cm6, the pulse width was selected to 3000μs, the reverse current density was set to -40mA / cm6, the pulse width was selected to 3000μs, the duty cycle was selected to 20%, and the deposition time was 10min. The precursor was annealed in a nitrogen atmosphere, the annealing temperature was set to 600℃, and the temperature was naturally cooled. After annealing, a copper / carbon nanotube composite material was formed with uniform distribution and excellent performance.

[0094] Embodiment 3:

[0095] First, 0.1 g of single-walled carbon nanotubes was added to 30 mL of mixed acid and stirred evenly, and then 4 g of nitric acid was added batch by batch and stirred continuously until a suspension was obtained. The suspension was heated and kept warm at 50-100 ° C for 0.5-12 h, then cooled to room temperature and poured into 100 mL of distilled water containing 1 mL of chromic acid. After that, the acid was removed by centrifugation and then washed with sulfuric acid to remove impurities. Finally, the complex was dispersed in deionized water and filtered to neutrality to obtain a 3 mg / mL distilled water dispersion of oxidized exfoliated carbon nanotubes.

[0096] Prepare an ethanol aqueous solution of 2M KOH and 0.5M NaHCO3, with a volume ratio of ethanol to water of 3:1. Immerse the polyimide PI film in the aforementioned solution for pretreatment for 30 minutes. Coat the PI surface with 0.4g / cm6 photocurable resin. Curing the photocurable resin under ultraviolet light for 2 hours to form a stable base film. Coat a colloidal solution containing noble metal acetate and noble metal chloride on the photocurable resin and dry it again.

[0097] Use pulsed electroplating technology to plate copper on the base film. Set the forward current density to 100mA / cm6, the pulse width to 3000μs, the reverse current density to -40mA / cm6, the pulse width to 3000μs, and the duty cycle to 20%. Carry out plating for 10 minutes to form a composite copper material. Mix 100mL of the single-walled carbon nanotube aqueous solution with the plating solution containing 60g / L copper ions, and control the pH value of the plating solution to 9.

[0098] Single-walled carbon nanotubes and copper ions were co-deposited on the base film using pulsed electrodeposition technology. The forward current density was set to 100mA / cm6, the pulse width was selected to 3000μs, the reverse current density was set to -40mA / cm6, the pulse width was selected to 3000μs, the duty cycle was selected to 20%, and the deposition time was 10min. The precursor was annealed in a nitrogen atmosphere, the annealing temperature was set to 600℃, and the temperature was naturally cooled. After annealing, a copper / carbon nanotube composite material was formed with uniform distribution and excellent performance.

[0099] Embodiment 4:

[0100] First, 0.1 g of single-walled carbon nanotubes was added to 30 mL of mixed acid and stirred evenly, and then 4 g of perchloric acid was added batch by batch and stirred continuously until a suspension was obtained. The suspension was heated and kept warm at 50-100 ° C for 0.5-12 h, then cooled to room temperature and poured into 100 mL of distilled water containing 1 mL of chromic acid. After that, the acid was removed by centrifugation and then washed with sulfuric acid to remove impurities. Finally, the complex was dispersed in deionized water and filtered to neutrality to obtain a 4 mg / mL distilled water dispersion of oxidized exfoliated carbon nanotubes.

[0101] Prepare an ethanol aqueous solution of 2M KOH and 0.5M NaHCO3, with a volume ratio of ethanol to water of 3:1. Immerse the polyimide PI film in the aforementioned solution for pretreatment for 30 minutes. Coat the PI surface with 0.4g / cm6 photocurable resin. Curing the photocurable resin under ultraviolet light for 2 hours to form a stable base film. Coat a colloidal solution containing noble metal acetate and noble metal chloride on the photocurable resin and dry it again.

[0102] Use pulsed electroplating technology to plate copper on the base film. Set the forward current density to 100mA / cm6, the pulse width to 3000μs, the reverse current density to -40mA / cm6, the pulse width to 3000μs, and the duty cycle to 20%. Carry out plating for 10 minutes to form a composite copper material. Mix 100mL of the single-walled carbon nanotube aqueous solution with the plating solution containing 60g / L copper ions, and control the pH value of the plating solution to 9.

[0103] Single-walled carbon nanotubes and copper ions were co-deposited on the base film using pulsed electrodeposition technology. The forward current density was set to 100mA / cm6, the pulse width was selected to 3000μs, the reverse current density was set to -40mA / cm6, the pulse width was selected to 3000μs, the duty cycle was selected to 20%, and the deposition time was 10min. The precursor was annealed in a nitrogen atmosphere, the annealing temperature was set to 600℃, and the temperature was naturally cooled. After annealing, a copper / carbon nanotube composite material was formed with uniform distribution and excellent performance.

[0104] Comparative Example 1:

[0105] Compared with Example 3, the only difference is that the PI film is not cured for 2 hours under ultraviolet light by the photocurable resin.

[0106] Comparative Example 2:

[0107] Compared with Example 3, the only difference is that single-walled carbon nanotubes and copper ions are co-deposited on the base film.

[0108] Previously, no copper plating step was performed.

[0109] Comparative Example 3:

[0110] Compared with Example 3, the only difference is that no distilled water dispersion of oxidized exfoliated carbon nanotubes is added.

[0111] Comparative Example 4:

[0112] Compared with Example 3, the only difference is that 20 mg / mL of the distilled water dispersion of oxidized exfoliated carbon nanotubes is added.

[0113] Comparative Example 5:

[0114] Compared with Example 3, the only difference is that 20 mg / mL of a distilled water dispersion of oxidized exfoliated graphene is added.

[0115] Comparative Example 6:

[0116] Compared with Example 3, the only difference is that 20 mg / mL of a distilled water dispersion of oxidatively exfoliated multi-walled carbon nanotubes is added.

[0117] Comparative Example 7:

[0118] Compared with Example 3, the only difference is that 20 mg / mL of the distilled water dispersion of oxidized exfoliated carbon fibers is added.

[0119] Table 1 Characterization results of composite copper materials

[0120]

[0121] Examples 1-4 illustrate that too few single-walled carbon nanotubes cannot effectively improve the mechanical properties of the alloy. Single-walled carbon nanotubes have high strength and rigidity. Adding an appropriate amount can enhance the strength and hardness of the alloy, but if the addition amount is too small, its enhancement effect may not be fully exerted. Too few single-walled carbon nanotubes affect the electrical conductivity of the alloy. Single-walled carbon nanotubes have excellent electrical conductivity. Adding an appropriate amount can improve the electrical conductivity of the alloy, but if the addition amount is too small, the electrical conductivity may not be significantly improved. Too many single-walled carbon nanotubes may cause the mechanical properties of the copper composite material to decrease. Excessive addition of single-walled carbon nanotubes may cause uneven grain refinement, thereby reducing the strength and hardness of the alloy. Secondly, too many single-walled carbon nanotubes may cause the electrical conductivity of the copper composite material to deteriorate. Although single-walled carbon nanotubes themselves have good electrical conductivity, excessive addition may increase the cross-linking between tubes, thereby reducing the overall electrical conductivity.

[0122] Compared with Example 3, the PI film in Comparative Example 1 was not cured by the photocurable resin under ultraviolet light, resulting in a significant decrease in the tensile strength of the copper composite material. The photocurable resin has good adhesion and bonding ability, can effectively connect the PI film and the copper composite material, and increase the overall structural stability. If the photocurable resin is not added, the bonding strength is weakened, the structural connection is weak and fatigue fracture problems are prone to occur, and there is a lack of filler reinforcement effect, thereby significantly reducing the tensile strength. Therefore, when using the copper composite material, a photocurable resin should be added to improve the overall performance.

[0123] Compared with Example 3, the reason why the tensile strength and resistivity decreased because the copper plating step was not performed before the co-deposition of single-walled carbon nanotubes and copper ions on the base film in Comparative Example 2 was that the copper ions could not be firmly fixed on the base film, thereby failing to form a firm conductive path, resulting in an increase in resistivity.

[0124] Compared with Example 3, no distilled water dispersion of oxidatively exfoliated carbon nanotubes was added in Comparative Example 3. Excessive single-walled carbon nanotubes may also cause a decrease in the electrical conductivity of the copper composite material. Although single-walled carbon nanotubes themselves have good electrical conductivity, excessive addition will increase the cross-linking between the tubes, thereby reducing the overall electrical conductivity.

[0125] Compared with Example 3, no distilled water dispersion of oxidatively exfoliated carbon nanotubes was added in Comparative Example 4. Excessive single-walled carbon nanotubes may also cause a decrease in the electrical conductivity of the copper composite material. Although single-walled carbon nanotubes themselves have good electrical conductivity, excessive addition will increase the cross-linking between the tubes, thereby reducing the overall electrical conductivity.

[0126] Compared with Example 3, the conductivity of the copper composite material decreased after adding the distilled water dispersion of oxidized exfoliated graphene, the distilled water dispersion of oxidized exfoliated multi-walled carbon nanotubes, and the distilled water dispersion of oxidized exfoliated carbon fibers in Comparative Examples 5-7, respectively. The electrical conductivity of graphene, multi-walled carbon nanotubes, and carbon fibers is not as good as that of single-walled carbon nanotubes. In addition, carbon fibers will make the product brittle, and the prepared composite copper material is not suitable for flexible electronic devices. Single-walled carbon nanotubes have more excellent electrical conductivity, which makes them have broad application prospects in many fields.

[0127] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A flexible electronic device with single-walled carbon nanomaterial modified copper metal attached to a polymer substrate, characterized in that: The invention comprises a polymer base film, a light-cured resin layer, a copper layer and a copper / carbon nanotube composite layer which are stacked.

2. The flexible electronic device according to claim 1, characterized in that: The coating dry weight of the photocurable resin layer is 0.2-1 g / cm 2 .

3. A method for preparing a flexible electronic device with single-walled carbon nanomaterial modified copper metal attached to a polymer substrate, characterized in that: The following steps are involved: 1) treating the single-walled carbon nanotubes with a strong oxidant to obtain a highly dispersed single-walled carbon nanotube aqueous solution; 2) coating the surface of the pre-treated polymer base film with a photocurable resin and curing it to form a stable base film; 3) using pulse electrodeposition technology to plate copper on the base film for a period of time to form a composite copper material; 4) adding the single-walled carbon nanotube aqueous solution into the electroplating solution, and using pulse electrodeposition technology to co-deposit the single-walled carbon nanotube aqueous solution with copper ions to form a precursor; 5) The precursor is annealed to obtain a copper / carbon nanotube composite material.

4. The preparation method according to claim 3, characterized in that: In step 1), after adding single-walled carbon nanotubes to the mixed acid and stirring evenly, perchloric acid or nitric acid is added batch by batch and stirring is continued until a suspension is obtained; the suspension is heated and kept at 50-100° C. for 0.5-12 hours, then cooled to room temperature and poured into distilled water containing chromic acid; thereafter, the acid is removed by centrifugation, and then washed with sulfuric acid to remove impurities; finally, the composite is dispersed in deionized water and filtered until neutral to obtain an oxidatively exfoliated carbon nanotube dispersion.

5. The preparation method according to claim 4, characterized in that: The mixed acid is composed of hydrochloric acid and phosphoric acid; the mass volume ratio of the single-walled carbon nanotube to the mixed acid, perchloric acid, nitric acid and chromic acid is 1g:100-600mL:1-8mL:30-50mL:4-25mL.

6. The preparation method according to claim 3, characterized in that: In step 2), the polymer base film is a polyimide (PI) film; the PI film is prepared by immersing it in a solution of 1-3M KOH and 0.5-2M NaHCO3 in an ethanol aqueous solution with a volume ratio of ethanol to water of 1-3:1 for 30-60 minutes; then a 0.2-1 g / cm2 dry weight film is coated on the surface of the PI film. 2 Light-curing resin, cures under ultraviolet light for 1-3 hours to form a stable base film.

7. The preparation method according to claim 3 or 6, characterized in that: In step 2), the photocurable resin is shielded by a light-shielding mask or template to form a photocurable area with a certain pattern or structure.

8. The preparation method according to claim 3, characterized in that: In step 3), a titanium plate with a surface polishing treatment is selected as the working electrode, and a copper plate is selected as the counter electrode. Electroplating is performed using a copper sulfate electroplating solution with a pH value of 7-9, and copper is deposited on the PI film using a pulse electrodeposition method.

9. The preparation method according to claim 3 or 8, characterized in that: In step 3), the oxidized exfoliated carbon nanotube dispersion is added to the electroplating solution, and is uniformly dispersed by ultrasonic and magnetic stirring for 30-60 minutes each. Finally, a copper / carbon nanotube composite precursor is prepared by pulse electrodeposition, and the electroplating solution is replaced regularly.

10. The preparation method according to claim 3, characterized in that: The deposition time of step 3) is 10 min, and the deposition time of step 4) is 10-60 min.

Citation Information

Patent Citations

  • Preparation method of wireless charging device capable of being sewn on fabric and device

    CN112865239A